Spinal Subdural Hematoma and Non-Accidental Head Injury - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The incidence of spinal pathology in 18 children with non-accidental head injury was determined in a study at Nottingham University Hospitals, UK.